Production Quality Development of Nipa Palm Bowl of Palian River Basin Community, Trang Province - Podkumnerd, Noppadon; Wunsri, Supranee; Khairin, Sujint (Area Based Development Research Journal, 2019)
The objective of this research is to upgrade the quality of Nipa palm bowl production of Palian river basin by using solar dryer technology. The study is performed with the participation of community in every step e.g. preparation of materials for testing, solar dryer testing and defect studies to improve technology efficiency. The Nipa palm bowl production capacity has been found to increase while the production time reduced from 1day to only 3 hours. The technology was employed by the community enterprise group, “Ban Na Yod Tong basketry”. The efficiency in Nipa palm bowl production increases from 1,300 to 17,000 pieces per month, or 12 times higher. The income of approximately 157,000 Baht per month has been generated to the group, making a total of 1,570,000 Baht in the period of 10 months. The researcher and the leader of the community have collaboratively established a network for Nipa palm bowl production in Palian river basin in which community members from different areas collectively produce Nipa palm bowls and sell to the group. Recently, the group has expanded and it comprises 20 members, from only 5 during the formation stage. The follow-up 8 months after completing the research project reveals that the community has formally adopted the technology. The group’s Nipa palm bowls sales count for 27,600 pieces per month, that is an increase of 26,300 pieces per month, which is 20 times higher than the prior production process. By using the technology, the group can generate an income of 2,104,000 Baht. At present, the group has 80 members. The total income of the Palian river basin community from using this technology calculated from July 2017-December 2018 is 3.77 million Baht. This can help the community reduce the waste from Nipa palm of 12 tons per year.